DEVELOPMENT AND ISO 25010 EVALUATION OF A WEB-BASED LABORATORY AND WORKSHOP INVENTORY SYSTEM - Muhammad Munir; Wulandari, Bekti; Rahman, Dzul Fadli; Fitriyanto, Doni; Dewanto, Satriyo Agung (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Effective management of laboratory tools and materials is essential to support experimentation and practical learning in higher education. However, many institutions still rely on manual inventory processes, which lead to data inaccuracies, inefficiencies, and limited monitoring capabilities. This study aims to develop and evaluate a web-based laboratory and workshop inventory management system tailored to the Department of Electronics and Informatics Education Engineering (DPTEI). The research adopts a Research and Development (R&D) design using the Waterfall Model, encompassing communication, planning, modeling, construction, and deployment phases. Data were collected from 22 participants (laboratory officers, workshop technicians, and lecturers) selected through purposive sampling. Requirement analysis was conducted via observations, structured interviews, and document review, while system evaluation employed questionnaires and automated testing tools. System quality was assessed using ISO 25010 criteria—functional suitability, reliability, performance efficiency, and usability—and a paired t-test was used to compare inventory management efficiency before and after implementation. The system achieved 100% functional suitability, very high reliability (up to 99.84% in stress testing), and strong performance efficiency with an average Largest Contentful Paint (LCP) of 1.180 seconds. The System Usability Scale (SUS) yielded a score of 84, classified as excellent, and the paired t-test (p = 0.002) indicated a significant improvement in inventory efficiency. These findings demonstrate that the developed system is robust, reliable, and well-accepted by users, contributing a domain-specific, empirically validated solution for digital resource management in academic laboratory settings.